Rancang Bangun Mesin Pemisah Kerupuk Mawar Guna Meningkatkan Output Pada Proses Pemisahan Kerupuk - Muhammad Naufal Ramadani; Erni Puspanantasari Putri (Jurnal Serambi Engineering, 2024)
Mr Rizal's MSME is located in Jerukgamping Village, Krian Sub-District, Sidoarjo Regency, East Java, processing the production of rose crackers from raw goods to finished products takes a maximum of 1 day and a maximum of 2 days. This is because there is a drying process that still relies on the sun's heat. The separation process Crackers that are done manually result in the resulting output not being optimal because the process takes quite a long time so it cannot be finished on the same day and must be continued the next morning. With the problems that occur in Mr. Rizal's cracker MSMEs, the researcher provides a solution to speed up the process of separating crackers that are still stuck to each other and only requires 1 worker. The solution used for the problems that exist in Mr. Rızal's rose cracker MSMEs is to carry out anthropometric and percentile calculations. which is used to determine the dimensions of the rose cracker separating machine. The cracker separating machine is designed using dimensions from anthropometry and the 50th percentile of workers so that it can be seen that the height of the machine frame is 103.5 cm, the diameter of the cracker separating tube is 67.25 cm, the height of the cracker exit path is 92.9 cm after it is done. In the experiment there was a comparison of the output of crackers that had been separated. The output before design was 113.5 kg, requiring 200 minutes with an output per minute of 0.6 kg. Meanwhile, the output after design was 150 kg, requiring 60 minutes with an output per minute of 2.5 kg.